2008
DOI: 10.1007/s11064-008-9718-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid Biosynthesis Regulates Sexually Dimorphic Fear and Aggressive Behavior in Mice

Abstract: The neurosteroid allopregnanolone is a potent positive allosteric modulator of GABA action at GABA(A) receptors. Allopregnanolone is synthesized in the brain from progesterone by the sequential action of 5alpha-reductase type I (5alpha-RI) and 3alpha-hydroxysteroid dehydrogenase (3alpha-HSD). 5alpha-RI and 3alpha-HSD are co-expressed in cortical, hippocampal, and olfactory bulb glutamatergic neurons and in output neurons of the amygdala, thalamus, cerebellum, and striatum. Neither 5alpha-RI nor 3alpha-HSD mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 132 publications
(274 reference statements)
0
110
0
Order By: Relevance
“…Furthermore, we demonstrated that the encounter with the sleeping intruder or exposure to a novel object did not increase locomotor activity in male isolation-reared mice ( Figure 4a). As social isolation does not induce aggressive behavior in female mice (Pinna et al, 2003(Pinna et al, , 2005(Pinna et al, , 2008, the present findings indicate that encounter-induced behavioral responses to emotional states, such as anxiety or fear, are observed selectively in male isolation-reared mice.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Furthermore, we demonstrated that the encounter with the sleeping intruder or exposure to a novel object did not increase locomotor activity in male isolation-reared mice ( Figure 4a). As social isolation does not induce aggressive behavior in female mice (Pinna et al, 2003(Pinna et al, , 2005(Pinna et al, , 2008, the present findings indicate that encounter-induced behavioral responses to emotional states, such as anxiety or fear, are observed selectively in male isolation-reared mice.…”
Section: Discussionmentioning
confidence: 46%
“…However, the mice were able to see, hear, and smell their neighbor. Thus, a social encounter with an unfamiliar conspecific through a mesh partition is considered a form of psychological stress, and it is useful for studies of the neurochemical changes that may be involved in the abnormal behaviors of isolation-reared animals (Ago et al, 2012;Fone and Porkess, 2008;Lukkes et al, 2009a, b;Pinna et al, 2008). In this study, the total time that the resident mice spent near the partition and the total time the resident and intruder mice spent interacting did not differ between the male group-reared, female isolation-reared, and male isolation-reared mice (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Open field activity was carried out according to a previously reported method with some modifications (Archer, 1977;Walsh, Cummins, 1976;Pinna et al, 2008). Thirty minutes after the administration of vehicle or test compound, a mouse was placed in the centre of a round open field of 30 cm diameter and 25 cm high, and the open field activity were measured during 6 minutes recording how many times the animal stays in the centre of the cage and the number of risings.…”
Section: Open Field Activitymentioning
confidence: 99%
“…This study was realized according to the method described by Pinna et al (2008). A group of animals was isolated in individual cage and other group remained grouped during six week.…”
Section: Aggressive Behavioursmentioning
confidence: 99%